Morphology of 925 Silver Powder Particles Produced From Gas Atomization - Montri Kawsuk; Surat Wannasrib; Sirichai Torsakula (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
In order to examine the impact of metal water temperature and gas flow rate on the production of 925 silver alloy powder via closed-coupled nozzle and gas atomization process with nitrogen gas as the production medium, and since the morphology of the powder particles could not account for the influence of these variables, the aim was to comprehend and propose a new approach for a general framework for studying the influence of such factors. As a consequence, an investigation was conducted into the impact of these two variables on the morphology, which was characterized by roundness values. Particle size and distribution information can be conveyed to facilitate interpretation. According to the results of the experiment, the gas flow rate and metal water temperature influence the particle morphology in terms of particle size and distribution with respect to roundness. The particle size distribution of metal powders is more restricted and the particle roundness increases. This is due to the fact that the particle morphology plays a critical role in determining which metal powder particles are suitable for forming metal powder workpieces via various production methods. The gas flow rate and metal water temperature influence the particle size distribution, roundness value, and significant size of 925 silver alloy powder.